A Description and Evaluation of Descriptive Glossary of Lexicography - Masoud Moshayedi; Mojtaba Maghsoudi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
In this study, the “Descriptive Glossary of Lexicography” compiled by Fariba Ghatreh has been described and evaluated. To do so, on the one hand, the formal appearance of the book concerning the principles of scientific writing has been taken into account, and on the other hand, the content of the book regarding the whatness and the importance of the materials presented has been scrutinized. Concerning the view that the author has been successful in compiling the first “Descriptive Glossary of Lexicography” in Persian, it is extremely valuable, but at the same time, some shortcomings meet the eyes while looking deeply into the book. From the formal point of view, mechanics of writing, proper use of some fonts and sizes for entries and subentries, italicizing or non-italicizing the entries, alphabetical order, reference system and layout of the pages, the book lacks some degree of inconsistency. From the content point of view, some faults are observed in the book, among which they can be referred to as the lack of crystal clear definitions for some entries, overlapping entries, the absence of some necessary terms in lexicography, some blind and confusing references and lack of examples and tables.